Cytologic features of a feline inductive odontogenic tumor - Leite-Filho, Ronaldo V.; Tagliari, Nelson J.; Grandi, Fabrizio [UNESP]; Laisse, Cláudio J. M.; Gerardi, Daniel G.; Pavarini, Saulo P. (Wiley, 2017)
The feline inductive odontogenic tumor (FIOT) is a rare entity among oral tumors in cats, the cytologic features of which are not well characterized but may prove useful. A fine-needle aspiration biopsy was performed on the right mandible between the permanent canine (404) and permanent fourth premolar (408) of an 8-month-old female mongrel cat. Cytologic smears showed epithelial cells and occasional spindle cells with extracellular homogenous acidophilic material in a hematic background. The initial diagnosis of benign tumor was confirmed by histopathologic examination of the biopsy specimen. This report describes the cytologic findings in a case of FIOT.
Keywords: Cat; odontogenic cell; oral tumor; rostral maxilla